Pleural effusion. Issue 961 (4th November 2005) - Medford, A; Maskell, N
Abstract : Pleural disease remains a commonly encountered clinical problem for both general physicians and chest specialists. This review focuses on the investigation of undiagnosed pleural effusions and the management of malignant and parapneumonic effusions. New developments in this area are also discussed at the end of the review. It aims to be evidence based together with some practical suggestions for practising clinicians.